PELATIHAN GURU PENDAMPING SISWA OLYMPIADE BAHASA JERMAN PADA LEVEL A2-GER - Karuna, Kalvin; Serpara, Henderika; Nikijuluw, Maria (German für Gesellschaft (J-Gefüge), 2024)
Community service activities are carried out with the aim of (1) increasing teachers' knowledge and understanding of the test format, especially the A2 test format developed by the Goethe Institut with reference to the Gemeinsamer Europäischen Referenzrahmen (GER), and (2) improving teachers' skills in using reading and writing strategies. using reading and writing strategies in solving reading and writing questions at the A2 level. Community service activities carried out by the German Language Education Study Program team are directed at two main focuses: (a) teachers' understanding of the A2 test format as a whole, and (b) German teacher skills in preparing students to understand texts and writing at the A2 level, as well as writing at the A2 level, as well as part of the preparation of students to face the German Olympiad selection. The method of implementing community service activities is carried out through the following stages: (1) The preparation stage begins with: coordination with partners, determination of activity schedules, preparation of training materials, registration of participants, (2) The implementation stage includes: analysis of the A2 level question format, which includes reading and writing, and interactive lectures through PPT interspersed with questions and answers, responses, and training. (3) The reflection and evaluation stage is used to obtain feedback on the overall training implementation, both in terms of organization and material achievement. The results obtained from this activity were that overall, the participants were satisfied with the implementation of the activity because the materials trained were in accordance with the learning needs at school, which could improve both pedagogical and linguistic abilities at least at the A2-Ger level.